2016
DOI: 10.5966/sctm.2015-0169
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CCAAT/Enhancer-Binding Protein β Expression With the Phosphodiesterase Inhibitor Isobutylmethylxanthine Improves Myoblast Engraftment Into Dystrophic Muscle

Abstract: This study demonstrates that treatment with isobutylmethylxanthine is an efficient method of expanding muscle progenitor cells, while preserving regenerative potential, before transplantation. Phosphodiesterase inhibitor treatment improves myoblast culture conditions in such a way as to reinvigorate myoblast transplantation as a viable therapeutic approach to halt muscle wasting in Duchenne muscular dystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 52 publications
(92 reference statements)
2
14
0
Order By: Relevance
“…C/EBPβ has been shown have high expression in MuSCs and declines during early differentiation (Marchildon et al, 2012). Overexpression of C/EBPβ has been shown to inhibit myogenic differentiation, while loss of C/EBPβ leads to precocious differentiation (Lala-Tabbert et al, 2016). These data highlight the role of C/EBPs in preserving the stem/progenitor cell chromatin state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C/EBPβ has been shown have high expression in MuSCs and declines during early differentiation (Marchildon et al, 2012). Overexpression of C/EBPβ has been shown to inhibit myogenic differentiation, while loss of C/EBPβ leads to precocious differentiation (Lala-Tabbert et al, 2016). These data highlight the role of C/EBPs in preserving the stem/progenitor cell chromatin state.…”
Section: Resultsmentioning
confidence: 99%
“…This non-swelling gel chemistry results in equivalent laminin protein concentrations (estimated to be 7.5 ng cm–2 in ref. 32) on both soft and rigid hydrogels. We cut and adhered all hydrogels to cover the surface area (2.0 cm2) of 24-well culture plates.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study examining human MuSC heterogeneity identified a population of CAV1+ MuSCs (CXCR4/CD29/CD56/CAV1) that were resistant to activation upon isolation and showed improved engraftment after transplantation, 48 a phenotype similar to C/EBPβ‐overexpressing primary myoblasts (Figure 3). 35 Thus, we next investigated the role of Cav1 in the C/EBPβ‐growth arrest phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…C/ EBPβ is a member of a transcription factor family that takes part in the cell migration process [3,12,18]. Induction of C/EBPβ in muscle stem cells enhanced their migration and contributed to muscle repair in dystrophic muscle [12]. C/EBPβ is an important mediator in endothelial migration during pathological angiogenesis [18].…”
Section: Discussionmentioning
confidence: 99%